CAFFEINE CONSUMPTION BEHAVIORS IN UNDERGRADUATES: A COVID-19 ERA STUDY - Ava , Grace Anderson (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
Caffeinated beverages have long been a staple among college students, with concerns arising over caffeine overuse in this population. This paper delves into the prevalence of caffeine consumption and its associated factors among college students. A recent survey conducted across five geographically dispersed United States universities revealed that a staggering 92% of surveyed students had consumed caffeine in the past year, signaling a worrisome trend of increasing caffeine intake. This surge in consumption can be attributed, in part, to a lack of education regarding the potential dangers of excessive caffeine consumption. Coffee emerged as the primary caffeinated beverage of choice among college students of all genders, underscoring its prevalence in this demographic. This study, titled "Intake of caffeine from all sources and reasons for use by college students," conducted by Mahoney et al. (2019), provided valuable insights into the demographics of college students who consume caffeine. Factors such as age, gender, family income, and ethnicity were examined to understand how caffeine consumption patterns vary among different groups within the college student population. It is worth noting that the Food and Drug Administration (FDA) acknowledges that caffeine can be a part of a healthy diet for most individuals. However, the FDA also emphasizes the potential health risks associated with excessive caffeine consumption, particularly in individuals with specific health conditions, such as varying body weights, medication use, and elevated stress levels. These factors underscore the need for a comprehensive understanding of caffeine consumption patterns and their potential health implications among college students.